Formation of the runoff of small rivers in a large city of the Volga basin (on the example of Nizhny Novgorod). - Sergey V. Yasinsky; Maria B. Alieva; Marina V. Shmakova (Водное хозяйство России: проблемы, технологии, управление, 2023)
The current state of the problem of the formation of the runoff of small rivers fl owing in large cities in the basin of the Volga River is considered (the city of Nizhny Novgorod as a study case). Small rivers perform two functions: they are part of the ecological framework and as fl ow systems, they remove large volumes of pollutants. One of the main environmental problems in cities in the Volga basin is the lack of state integrated geo/ecological monitoring, including monitoring of hydrological and geochemical processes that determine the hydrological and hydro/chemical regimes of small rivers. The absence of such monitoring does not allow executive powers to carry out and plan scientifically based nature and water management activities on the territory of these cities, to predict the occurrence of extreme situations and eliminate their consequences.